Frequency and clinical implications of metabolic syndrome in different rheumatic diseases: Relationship with disease activity and severity - Suzan Sadek Al-Adle; Passant Nabil El-Husseiny; Nahla Naeem Eesa; Tamer A Gheita (Ulusal Romatoloji Dergisi)
Objective: To assess the frequency of metabolic syndrome (MetS) in various rheumatic diseases and to depict its association with disease characteristics, activity, and/or severity. Methods: Two hundred fifty-seven patients [47 rheumatoid arthritis (RA), 100 systemic lupus erythematosus (SLE), 49 systemic sclerosis (SSc), 33 axial spondyloarthritis (axSpA), and 28 vasculitis (21 with primary vasculitis and 7 with Behçet’s disease (BD)] and 70 controls were recruited, with a suitable number of controls matched for each corresponding disease. Demographic data, body mass index, waist circumference, comorbidities, and clinical and laboratory data were collected. Disease activity and/or severity were determined. MetS was defined according to the Adult Treatment Panel criteria. Results: In RA, MetS was comparable to the control group with no significant association to the disease activity score (p=0.33), but there was a significant difference according to the activity grading (p=0.007). In SLE, MetS was significantly more frequent (42%) versus the control (14.9%) (p=0.001) and was significantly related to disease activity (p=0.001). In SSc, axSpA, and vasculitis, the frequency of MetS was comparable to their corresponding controls (p=0.24, p=0.4, p=0.08) and was not related to their disease activity scores (p=0.7, p=0.4, p=0.97; respectively), as well as p=0.45 and p=0.14 for BD activity and damage. When comparing the different rheumatic diseases, MetS was significantly more frequent in SLE (p=0.04). Regarding MetS components, there was a significantly higher frequency of hypertension (p<0.0001) and significantly higher triglycerides (p=0.004) in SLE versus the other rheumatic diseases. No significant association was found between neutrophil-lymphocyte ratio and platelet-lymphocyte ratio with MetS in RA (p=0.4, p=0.4), SLE (p=0.35, p=0.73), SSc (p=0.46, p=0.14), axSpA (p=0.35, p=0.45) and vasculitis (p=0.72, p=0.29). Conclusion: MetS is frequently associated with rheumatic diseases, being significantly more frequent in SLE, and could be related to disease activity.